Spectral theory of linear differential operators and comparison algebras - Cordes, H. O. (Heinz Otto), 1925- (London Mathematical Society lecture note series, 1987)
The main aim of this book is to introduce the reader to the concept of comparison algebra, defined as a type of C*-algebra of singular integral operators.